2020
DOI: 10.1097/prs.0000000000007325
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Timing for Reduction Mammaplasty in Adolescents

Abstract: Background: Reduction mammaplasty effectively alleviates symptoms and restores quality of life. However, operating on adolescents remains controversial, partly because of fear of potential postoperative breast growth. This cross-sectional study provides surgeons with a method to predict the optimal timing, or biological “sweet spot,” for reduction mammaplasty to minimize the risk of breast regrowth in adolescents. Methods: The authors reviewed the medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…18 Moreover, our macromastia severity value calculation normalizes breast resection mass to body surface area, and therefore minimizes the likelihood of large body habitus confounding our assessment of hypertrophy severity. 11 The role of adipose tissue as an important endocrine organ cannot be discounted. Research investigating gynecomastia (male breast hypertrophy) demonstrates that increased amounts of adipose tissue may lead to excess aromatization of androgens and a downstream elevation of local estrogen production, stimulating mammary glandular proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Moreover, our macromastia severity value calculation normalizes breast resection mass to body surface area, and therefore minimizes the likelihood of large body habitus confounding our assessment of hypertrophy severity. 11 The role of adipose tissue as an important endocrine organ cannot be discounted. Research investigating gynecomastia (male breast hypertrophy) demonstrates that increased amounts of adipose tissue may lead to excess aromatization of androgens and a downstream elevation of local estrogen production, stimulating mammary glandular proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Using the method developed by Nuzzi et al, 11 the total breast resection mass (in grams) recorded intraoperatively at the time of surgery was divided by each patient's body surface area (m 2 ) to yield a macromastia severity value (g/ m 2 ). This effectively normalizes measurements of breast hypertrophy with respect to patient body habitus.…”
Section: Macromastia Severity Valuementioning
confidence: 99%
“…Interestingly, the authors also observed that breast size stabilizes considerably later in obese macromastia patients compared to healthy-weight or overweight women. 10 Although breast size stabilizes on average 3 years after menarche in healthy-weight and overweight patients, breast growth in obese macromastia patients may not end until 9 years after menarche. Performing reduction mammaplasty in young obese women before 9 years postmenarche was associated with a significantly higher odds of postoperative breast growth (OR, 1.19).…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7] In addition, obesity increases the risk of macromastia severity in the adolescent and young adult populations. [5][6][7] The reasons for presentation, and the patient-reported outcomes following reduction mammaplasty, are similar in obese and healthy-weighted adolescents and young adults. 3 Unlike findings in the adult population, surgical complications following breast reduction in adolescence and young adulthood seem independent of body mass index (BMI) category as well.…”
Section: Introductionmentioning
confidence: 99%
“…Symptomatic macromastia has been strongly associated with obesity, with roughly twothirds of breast patients presenting for consultation being overweight or obese. [2][3][4][5][6][7] In addition, obesity increases the risk of macromastia severity in the adolescent and young adult populations. [5][6][7] The reasons for presentation, and the patient-reported outcomes following reduction mammaplasty, are similar in obese and healthy-weighted adolescents and young adults.…”
Section: Introductionmentioning
confidence: 99%